Estrutura de comunicação digital para estudantes de engenharia no interior da Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
When World Health Organization (WHO) declared the COVID-19 outbreak a pandemic, drastic measures were taken worldwide in order to prevent the spreading of the virus. Thus, Brazil was forced to adopt social distancing measures as most of World’s countries. Such a course of action included the suspension of “in-person” higher education classes which were replaced instead by teaching mediated by digital tools. Therefore, transition to distance learning called for the implementation of technological and educational instruments in order for students and professors to adapt to remote teaching. Consequently, the great majority of Brazilian learning institutions were urged into developing communication structures that would facilitate the academic-administrative management of undergraduate courses. This work proposes a communication structure based on digital tools to reduce distance between students and university. In particular, the foundations of digital transformation and their applications to university management were investigated. Then, digital tools were employed to maintain education-related communication media as well as to manage regular events held by faculty boards. The project focused on three main objectives: (i) informative communication performed by means of a popular social media (Instagram), (ii) website development, (iii) organization of the IV Science and Technology Week. Metrics and results generated by this communication structure are presented. Finally, overall results concerning the different stages of the project are discussed.
Keywords: Covid-19; Comunicação - Ensino; Marketing digital; Redes sociais; Ensino remoto; Transformação digital; CNPQ::CIÊNCIAS EXATAS E DA TERRA